Are active labour market policies effective in activating and integrating low-skilled individuals?: an international comparison - Escudero, Verónica (Geneva, 2015)
"This paper examines the effectiveness of active labour market policies (ALMPs) in improving labour market outcomes, especially of low-skilled individuals. The empirical analysis consists of an aggregate impact approach based on a pooled cross country and time series database for 31 advanced countries during the period 1985–2010. A novelty of the paper is that it includes aspects of the delivery system to see how the performance of ALMPs is affected by different implementation characteristics. Among the notable results, the paper finds that ALMPs matter at the aggregate level, both, in terms of reducing unemployment, but also in terms of increasing employment and participation. Interestingly, start-up incentives are more effective in reducing unemployment than other ALMPs. The positive effects seem to be particularly beneficial for the low-skilled. In terms of implementation, the paper finds that the most favourable aspect is the allocation of resources to programme administration. Finally, a disruption of policy continuity is associated with negative effects for all labour market variables analysed."